Automation and Machine Learning in Transforming the Financial Industry - Donepudi , Praveen Kumar (Asian Business Review, 2019)
The major purpose of this study was to analyze the influence of machine learning on the digital age, particularly in the field of finance. This study involves the application of machine learning, its challenges, opportunities and effect on job openings and operations. This paper is based on the findings of a qualitative study of the text on the subject of machine learning in finance. The theoretical portion of this paper explores the universal framework, such as the past, existing and the next level of the machine learning, with emphasis on its advantages and drawbacks. The study also examines the global recognition of machine learning in the review of artificially intelligent development and start-ups in European countries. The research methodology used in this study was the evaluation of the qualitative methods in the paper. The study also reviewed twenty electronic records and articles on machine learning in finance. During the research on how computer technology transforms the banking sector, the implementation and impact of artificial intelligence in financing was discussed. Research shows that several financial institutions have significantly benefited from the introduction of a variety of machine learning and artificial intelligence. This paper demonstrates that there is a lack of experience in the field of machine learning, even as many unskilled or semi-qualified tasks carried out by individuals are carried out by machines. This study has shown that, through banking and financial valuation, whether it is manufacturing, data analysis or continuing to invest, there will be many more developments that can get the job done.